2015
DOI: 10.3329/jdmc.v22i2.21521
|View full text |Cite
|
Sign up to set email alerts
|

Role of chest X-ray in tuberculous cervical lymphadenitis

Abstract: Abstract:Tuberculous cervical lymphadenitis is not an uncommon entity when it comes to otolaryngology practice in Bangladesh. This study was done in the department of ENT and Head Neck Surgery, Dhaka Medical College Hospital, Dhaka, from January 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our findings were in agreement with in one study by Shah et al in Dhaka. 14 There was a satisfactory correlation between cytological and radiological findings.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings were in agreement with in one study by Shah et al in Dhaka. 14 There was a satisfactory correlation between cytological and radiological findings.…”
Section: Discussionmentioning
confidence: 74%
“…Single cervical lymphnode enlargement observed in study done at Dhaka medical college hospital was (40.44%) contrast to our study where single node enlargement is seen in (77.1%) 14 . In same study abnormal chest X-ray was found in (27.87%) cases while in study of cervical tuberculous lymphadenitis done at Government Medical College hospital Chandigarh, India; chest lesions on radioghraphy were evident in 16% of the patients 14,15 .…”
Section: Discussionmentioning
confidence: 94%
“…In the study of Karim F, it was found that out of 673 Chest X-rays, 26 were found positive for tuberculosis and it was a community based study 24 . Shah R delineated in their study that they found normal CXR in 132 cases (72.13%) and abnormal CXR was found in 51 cases (27.87%) and was done in ENT department of a hospital 25 .…”
Section: Discussionmentioning
confidence: 96%